Advanced Glycation End Products-induced Vascular Calcification is Mediated by Oxidative Stress: Functional Roles of NAD(P)H-oxidase - Tada, Y.; Yano, S.; Yamaguchi, T.; Okazaki, K.; Ogawa, N.; Morita, M.; Sugimoto, T. (Hormone and Metabolic Research, 2013)
Vascular calcification, especially medial artery calcification, is associated with increased morbidity and mortality in patients with diabetes mellitus and end-stage kidney disease. Advanced glycation end products (AGEs) accumulated in these patients may be associated with vascular calcification, although their actions are obscure. Since AGEs can induce oxidative stress, which leads to vascular damage, we investigated an in vitro study to elucidate the effects of AGEs and the roles of NAD(P)H oxidase in the pathogenesis of vascular calcification. A7r5, rat vascular smooth muscle cells (VSMCs) were incubated in calcification medium with glycolaldehyde-derived AGE (AGE3) to measure calcium deposition and 8-hydroxydeoxyguanosine (8-OHdG) and to determine mRNA levels of osteopontin (OPN), osteocalcin (OCN), Runx2, Nox-1, Nox-4, and p22phox by real-time PCR. Calcium deposition was increased by AGE3 in a dose-dependent manner (100–300 μg/dl) in A7r5 cells. Expression levels of Runx2, OPN, and OCN mRNAs were significantly higher in AGE3 treatment than those in control BSA. Increased 8-OHdG concentration in the culture medium and higher expression of Nox-1, Nox-4, and p22phox mRNAs (3–6-fold) were observed in cells treated with AGE3. AGE3-stimulated calcium deposition was significantly decreased in the cells transfected by either small interfering RNA for Nox-4 or p22phox, compared to the controls. In contrast, no significant effect was shown in silencing of Nox-1. Excessive oxidative stress and osteoblastic transition of VSMCs are involved in the pathogenesis of AGEs-induced vascular calcification. NAD(P)H oxidase plays important roles in this process.
Keywords: diabetes; vascular calcification; oxidative stress; NADPH oxidase; vascular smooth muscle